Optimization Of Sprinkler Spacing Under Wind Influence: Mathematical Modeling And Analysis - Khudayarov Zafarjon Jumaevich (Periodica Journal, 2025)
This article analyzes, based on theoretical modeling, the influence of wind speed and water droplet diameter on the coverage distance in sprinkler irrigation systems. The trajectory of a water droplet is expressed through mathematical equations that account for aerodynamic forces and wind effects. Based on the obtained results, the dependence of the center-to-center distance between sprinklers (S) on wind speed and droplet diameter was analyzed graphically. The results showed that as wind speed increases, the coverage distance decreases significantly, and smaller droplets tend to deviate more. Considering that the average wind speed in Uzbekistan ranges from 2–5 m/s, it was determined that the optimal distance between sprinklers should be in the range of 8–12 meters. The research findings have practical significance for the design and efficiency improvement of sprinkler irrigation systems.
Keywords: Sprinkler irrigation; sprinkler system; water droplet